The Efficacy of Dexamethasone in Reducing Postoperative Shivering after Caesarean Section Under Spinal Anesthesia: A Randomized Controlled Trial - Kalawa, Ariyachart; Wongseeda, Sasiprapa (วารสารวิชาการสุขภาพและสิ่งแวดล้อม, 2025)
This randomized, triple-blind controlled trial aimed to evaluate the efficacy of prophylactic dexamethasone 0.15 mg/kg in preventing postoperative shivering in 186-term pregnant women scheduled for cesarean section under spinal anesthesia. Participants were computer-randomized with concealed allocation. The treatment group received dexamethasone 0.15 mg/kg diluted to 10 ml while the control group received normal saline 10 ml, both administered by blinded anesthesia nurses. Data were analyzed using repeated measures ANOVA for temperature changes and Fisher's exact test for shivering incidence. The results showed that dexamethasone significantly reduced the incidence of postoperative shivering (12.90% vs 27.96%, p = 0.010), with a relative risk reduction of 53.85% and the number needed to treat 7. The dexamethasone group maintained significantly higher core temperatures (mean difference 0.376°C, p < 0.001) and required less rescue pethidine (3.23% vs 16.13%, p = 0.005). Both groups showed similarly low rates of postoperative nausea and vomiting (1.08% vs 2.15%, p = 0.50), and no surgical site infections were observed during the follow-up period. These findings suggest that prophylactic dexamethasone 0.15 mg/kg effectively reduces postoperative shivering in cesarean section under spinal anesthesia with a favorable safety profile. This intervention could be considered for incorporation into routine care protocols for eligible patients.